Frauen in Schwarz - Solomun, Zoran; Reidemeister, Helga (Germany : Ohne Gepäck Filmproduktion, 1997)
In Belgrade, "Women In Black" silent vigils were held weekly from 1991 to 1997 to protest nonviolently against the war; the Serbian regime's policy; nationalism; militarism and all forms of hatred, discrimination and violence.They support deserters from every former Yugoslavian republic, organize actions to support refugees and publish books and magazines.

The film portraits some of these strong personalities in form of travel notes that end with the last international congress of "Women in Black" in the summer of 1996 and the massive demostrations in the winter of 1996/97.
Keywords: Documentary films